Heat dissipation in ball grid array packages - Ying, Teck Mun. (2008)
This thesis discusses the issue of thermal management in typical Ball Grid Array (BGA) packages. It aims to study the behavior of heat dissipation in a single BGA solder joint as well as multiple solder joints through the use of analytical, numerical and experimental techniques. Important factors that contribute to the heat dissipation of BGA packages are analyzed and discussed. Such factors include geometrical condition, material properties and thermal loading on the BGA package.